Evidence for a Possible Existence of Icon-Painting and Book-Binding Workshops at Sysert Factories of 18th Century - Elena P. Pirogova (Вестник Екатеринбургской духовной семинарии, 2023)
The article is devoted to the analysis of the available data indicating the possible existence of workshops for the production of book bindings and icons on the territory of the factories at the Sysert mining district of A. F. Turchaninov. The author provides documents of the 1759 Inventory of the three main churches of the district: Simeono-Anninskaya in Sysert, Petropavlovskaya in Polevskoy and Troitskaya in Seversky factories, published in the 19th century, where the icons of “local painting” are indicated, and the name of one of the icon painters is given. The questions of who painted the icons for the Ekaterinburg churches in the first decades of the existence of this mining city, and where these people came from, are also considered. As the author found out, one of them, a teacher of the Ekaterinburg Drawing school, painted “holy images” with his students in the Sysert church. The main source of the study carried out in the article is the Property Inventory of 1789, compiled after the death of the plant-owner A. F. Turchaninov. It reveals and systematizes information on icons, concluding that many of them were painted by Ural masters, and the existence of Turchaninov’s own icon painters is not ruled out. This is supported by the information about a “drawing” school in Sysert, where artists and “painters” could be trained, for which there was not only the necessary educational literature, but also a rare Western European Piscator Bible — an illustrated edition of the 17th century, commonly used as an example of the plots of icons and iconographic compositions. The existence of A. F. Turchaninov’s own artists is confirmed by examples from the Inventory of paintings with local subjects, as well as documentary evidence of a contemporary — Academician N. Ya. Ozeretskovsky, with the facts of teaching A. F. Turchaninov’s working people various “arts” and crafts. Based on the systematization of the book bindings from the richest library of A. F. Turchaninov described in detail in the Inventory, a reasonable assumption is made about the places of their manufacture: not only by foreign bookbinders in the capital, but also by local craftsmen. The author does not yet have exact information about the presence of Turchaninov own bookbinding workshop, but the Inventory lists equipment that can be regarded as bookbinding.